Komodifikasi Agama pada Perumahan Syariah di Surabaya - Yelly Elanda (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2019)
Syariah housing has now penetrated the city of Surabaya. The syariahisation project is a form of the commodification of religion that marries business and religious symbols. The rise of syariah housing will result in spatial and social segregation. This paper will discuss the forms of the commodification of religion in syariah housing and the impact of the commodification of religion in syariah housing in the Surabaya area. This research uses descriptive qualitative method. Data collection techniques through literature studies by collecting all material or data that corroborate and are related to the study of sharia housing and the commodification of religion. The results of this study indicate that there are four forms of the commodification of religion in syariah housing. First, from the facilities offered by the use of religious labels in the form of an Islamic environment, there are regular studies, tahfidz houses, mosques, archery areas. Second, the marketing strategy by using a tagline that contains elements of Islam; inviting customers to the concept of religious seminars, using the names of housing that is closely attached to the nuances of Islam. Third,